Simplified and advanced simulation methods for prediction of fabric draping - Pickett, Anthony K.; Creech, Gavin; de Luca, Patrick (European Journal of Computational Mechanics, 2005)
Three principle methods are available for fabric draping analysis; namely, simplified “mapping” and Finite Element methods applied at the macro- and meso- levels. The mapping method was first introduced in the 1950’s and due to its simplicity is still the preferred technique for industrial work. During the past decade Finite Element methods have evolved that offer significant improvements in terms of accuracy and range of application. This method can allow definition of the forming system, friction and permit material laws valid for a wide range of fabric types. Two levels of fabric modelling are possible; first, macro-models which approximate the fabric as a homogeneous continuum and, second, more complex meso- models that accurately represent fabric architecture and thereby the complex deformation mechanisms. This paper gives an overview of these techniques, their limitations and the state-of-the-art.